2014
DOI: 10.3109/02770903.2014.990092
|View full text |Cite
|
Sign up to set email alerts
|

Urinary leukotriene E4 levels in atopic and non-atopic preschool children with recurrent episodic (viral) wheezing: a potential marker?

Abstract: U-LTE4 is strongly associated with the acute wheeze episode in preschool children, more so in atopics. Increased basal levels of U-LTE4 occur only in atopics. This suggests a potential role of U-LTE4 as a marker of atopic, virus-induced asthma in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…There are higher levels of U-LT inacute wheeze episode in preschool atopic children, compared to non-atopic. [ 90 ] The measurement of U-LT could be a non-invasive method for atopic predisposition and diagnosis and management of asthma in preschool children. [ 91 ] It is known that environmental tobacco smoke exposure is associated with higher U-LT.[ 92 ]…”
Section: Other Biomarkersmentioning
confidence: 99%
“…There are higher levels of U-LT inacute wheeze episode in preschool atopic children, compared to non-atopic. [ 90 ] The measurement of U-LT could be a non-invasive method for atopic predisposition and diagnosis and management of asthma in preschool children. [ 91 ] It is known that environmental tobacco smoke exposure is associated with higher U-LT.[ 92 ]…”
Section: Other Biomarkersmentioning
confidence: 99%
“…The reason for wheezing in atopic children with Adv pneumonia may be related to the exposure of the damaged airway epithelium neurons and increased airway sensitivity (20). Studies have shown that leukotriene E4 is strongly associated with episodes of acute wheezing in preschool children, and that higher levels of leukotriene E4 are present in the airways of atopic children than in the airways of nonatopic children (21); therefore, atopic children are more prone to wheezing. In contrast, it may also be related to the characteristics of Adv infection.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have already been carried out in children to identify allergy markers in less invasive biologic fluids like urine and saliva . However, for both urine and saliva, one should be aware that analysis of biomarkers may run into some issues ranging from the fact that it does not reflect the source of the biomarker, the difficulty of adequate result expression, and method and timing of collection can have an enormous impact on the results.…”
Section: Biomarkers For Allergy In Other Biologic Fluidmentioning
confidence: 99%